2003
DOI: 10.1016/s0147-6513(02)00071-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mercury on the feeding behavior of fathead minnows (Pimephales promelas)

Abstract: Fathead minnows (Pimephales promelas) were exposed to mercury (1.69, 6.79, and 13. 57 microg/L HgCl(2), 10 days exposure), and afterward their foraging ability was tested in a vegetated habitat for 7 days. Among the foraging metrics used were foraging efficiency, capture speed, and the ability to learn and retain information regarding habitat characteristics. In addition to behavioral tests, muscle tissue acetylcholinesterase activity and brain levels of several neurotransmitters were investigated. Comparisons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…All exposure regimes used in this study were sublethal, were similar to those used with other fish species, represent environmentally relevant concentrations, and produced similar LC 50 s for embryo exposures [4247]. Although several studies have indicated greater MeHg uptake in fish than observed in this study [4750], none of those involved developmental exposures targeted at and isolated to the earliest stages of embryonic neuron formation (the first 24 hpf in zebrafish).…”
Section: Discussionmentioning
confidence: 78%
“…All exposure regimes used in this study were sublethal, were similar to those used with other fish species, represent environmentally relevant concentrations, and produced similar LC 50 s for embryo exposures [4247]. Although several studies have indicated greater MeHg uptake in fish than observed in this study [4750], none of those involved developmental exposures targeted at and isolated to the earliest stages of embryonic neuron formation (the first 24 hpf in zebrafish).…”
Section: Discussionmentioning
confidence: 78%
“…Successful feeding is influenced by motivation (frequency of strikes), search effectiveness, selection, orientation, coordination, capture success, and handling time (Scharf et al 1998;Buckel et al 1999a;Buckel et al 1999b;Weis et al 2001;Weis et al 2003). Fathead minnows exposed to high concentrations of mercury had impaired foraging efficiency, increased pause time, and decreased capture speed (Grippo and Heath 2003). In some studies, frequency of strikes was more sensitive to contaminants than actual prey capture, suggesting that motivation was more affected than coordination as Brown and Johansen (1987) found with pentachlorophenol-treated fish.…”
Section: Bluefish Behavior and Sizementioning
confidence: 99%
“…Hamers and Krogh 1997;Power 1990). Grippo and Heath (2003) detected the effects of mercury on the foraging efficiency and capture speed of fathead minnows (Pimephales promelas) exposed to 13 and 57 lg/l HgCl 2 . The prey capture rate of mummichogs (Fundulus heteroclitus) in the laboratory was closely related to the diet of the fish in the field, thus representing a biomarker with high ecological relevance.…”
Section: Introductionmentioning
confidence: 99%